Pasien Pleuritis TB Terkonfirmasi ADA Test Dengan Efusi Pleura Massif Yang Mendapat Penanganan Chest Tube, WSD, dan OAT - Wibowo, Imam Mukti; Sahrun (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Tuberculosis (TB) is one of the oldest infectious diseases that has existed throughout the history of human civilization and remains a major public health problem in the world today. Tuberculosis is caused by Mycobacterium Tuberculosis which can result in TB Pleuritis, which is inflammation of the pleura, both the parietal pleura and the visceral pleura, manifested by accumulation of fluid in the pleural cavity. A 20-year-old man came with complaints of coughing for the past 1 month, white phlegm, shortness of breath felt worse for the past 2 days, fever not too high for the past 1 week accompanied by cold sweats at night. The patient feels that it is difficult to gain weight and tends to lose weight this month. Chest X-ray show left massive pleural effusion. Acid fast baccili sputum was negative. USG Thorax show pleural fluids approximately 1600 cc.  Tuberculosis (TB) can cause TB pleutiritis with symptoms of shortness of breath and sometimes chest pain on the side of the pleural cavity where there is fluid.3 Treatment of TB Pleuritis is the same as the treatment of pulmonary TB in general with the 2RHZE/4RH combination. Optimal fluid evacuation is carried out according to the patient's condition.